Increased diagnostic sensitivity of palpation‐guided thyroid nodule fine‐needle aspiration cytology by BRAF V600E‐mutation analysis - Oliver Gimm; Kristin Ivansson; Ervin Beka; Hugo M Rossitti; Stina Garvin; Peter Söderkvist (Wiley, 2021)
Abstract Papillary thyroid carcinoma (PTC) is the most common type of thyroid cancer and its incidence is increasing. Preoperative diagnosis is warranted in order to avoid 'two‐stage' procedures that are associated with additional costs and higher radioactive iodine remnant uptake. In the setting of thyroid cancer, somatic BRAF V600E‐mutations are highly specific for PTC and can be analyzed in aspirates from fine‐needle aspiration cytology (FNAC). The 'gold standard' to perform FNAC is ultrasound guidance. Here, we analyze whether adding BRAF V600E‐mutation analysis could be of value in palpation‐guided FNACs. A total of 430 consecutive patients were included. Ultrasound‐guided FNACs were performed in 251 patients and 179 patients underwent palpation‐guided FNACs. BRAF V600E‐mutation analysis was performed using two methods, an allele‐specific polymerase chain reaction (PCR) analyzed by capillary gel electrophoresis (PCR/Qiaxcel), and a droplet digital PCR (ddPCR) assay. A total of 80 patients underwent surgery, and histology revealed 25 patients to have PTC. Of the 25 PTCs, 23 (92%) showed a BRAF V600E‐mutation. Both mutation analysis methods (PCR/Qiaxcel and ddPCR) produced concordant results. In the ultrasound‐guided group, the preoperative diagnostic sensitivity of FNAC using the Bethesda classification alone was very high and additional BRAF V600E‐mutation analysis added little to the preoperative diagnostic sensitivity. By contrast, in the palpation‐guided group, by adding BRAF V600E‐mutation analysis, eight instead of four patients were diagnosed of having PTC. This increase in the diagnostic sensitivity was statistically significant (p < 0.05). The costs per sample were as low as 62 USD (PCR/Qiaxcel and ddPCR) and 35 USD (PCR/Qiaxcel only). Ultrasound‐guided FNAC should be aimed for when dealing with thyroid nodules. However, if palpation‐guided FNAC cannot be avoided or may be required due to resource utilization, adding BRAF V600E‐mutation analysis using the methods described in this study might significantly increase the proportion of preoperatively diagnosed PTCs. The additional costs can be considered very reasonable.